Pattern of paediatric maxillofacial fractures in Lagos, Nigeria - M. O. OGUNLEWE, O. JAMES, A. L. LADEINDE & W. L. ADEYEMO (Paediatric Dentistry, 2006)
Maxillofacial fractures in children are proportionally rare when compared to those occurring in adults [1–6].